Conocimiento y comportamiento comunitario respecto a la calidad del agua tratada en San José de Lupuna, Iquitos, Loreto, 2024 - Saavedra Lopez, Danna Dayanh (2024)
The objective of the research was to evaluate the level of community knowledge and behavior regarding the quality of water treated by the Living Water Treatment System (STAV) in San José de Lupuna, Iquitos, and its impact on improvements in water consumption and management in the families of the community. The methodology used was descriptive quantitative, with a non-experimental design and a cross-sectional approach, using surveys to collect data on the perception, knowledge and practices of the inhabitants regarding treated water. The results revealed that 94% of the respondents have a positive perception of the quality and safety of treated water, although only 35% "Totally agree" with the organoleptic characteristics of the water, such as taste and smell. 64% of the participants demonstrated solid knowledge about the risks associated with the consumption of untreated water, although 10% remain "Neutral" regarding information on the efficient storage and use of water. Regarding community behavior, 74% "Totally agree" with the recommended practices for the use of treated water, while 23% exhibit low-level behavior. Finally, 76% of the community recognized that efficient water management has improved their quality of life, although the need for improved maintenance and ongoing education was stressed. It is concluded that, although the general perception is positive, there are areas for improvement in the organoleptic characteristics of water and in the dissemination of information on its storage and use. In addition, it is necessary to strengthen community practices and participation in the management of the water system to ensure long-term sustainability.